Assessing Readiness for e-Health in Egypt : A Case study of Cairo University Hospitals - Stadelmann, Jessica (AUC Knowledge Fountain, 2012)
Implementing E-Health can improve quality of care by increasing accessibility to patient health records, improving governance and administration, and integrating health information into an organized system. However, before implementation occurs, E-Readiness Assessment is an important tool used to evaluate an organization's likelihood of successful adoption. Cairo University Hospitals are still in early stages of implementation, and measures to improve E-Readiness would contribute to the transition from an almost complete lack of health information accessibility to successful adoption of an electronic system. This paper discusses how Cairo University Hospitals would be able to raise the quality of service delivery through E-Readiness and successful implementation of E-Health. Through information gathered from health officials and a case study of Cairo University Hospitals, the benefits of E-Health are reviewed and recommendations for adoption of E-Health are made.